Policing illicit drug abuse amongst the youth in Soweto - Mathosa, Francina (Acta criminologica, 2017)
This article investigates whether the implemented strategies sought to turn youth attitudes against illicit drug use had yielded the required results as expressed by the participants in the Jabavu and Moroka Townships in Soweto, South Africa. With an understanding that the efforts to reduce the prevalence of illicit drugs amongst the youth will not be successful if tackled by one or by a few role players, this article investigates the effectiveness or otherwise of a partnership between the relevant role players towards strengthening communities to prevent drug use among the adolescents. Four Focus group discussions (FGDs) were conducted with thirty-six participants. This comprised of ten police officials from the Moroka Police Station, eight members from the South African National Council on Alcoholism and Drug Dependence (SANCA) officials, ten representatives from the local Community Police Forums (CPFs) as well as eight lecturers from the South West Gauteng Technical and Vocational Education and Training College in Soweto. The first FGDs were conducted with SAPS officials selected from a pool of Police Act (Act 68 of 1995) personnel who perform operational duties, crime prevention, community service centres and sector policing in this area. The second FGDs were conducted with SANCA officials who work with the addicted youth. The third FGDs involved the representatives, the local CPF and the fourth FGDs consisted of, teachers from the South West Gauteng Technical and Vocational Education and Training College. The results of this article indicated that the required collaboration is seen as a key strength of the identified strategies by all four FGDs participants, SAPS, SANCA, CPF and lecturers. It was found that the majority of the participants indicated that they did not feel confident that they could deliver effective substance abuse prevention strategies to the youth. Based on the findings of this article, it is recommended that youth focused prevention initiatives include school-based and skills training programmes for the adolescents; monitoring and evaluation of the effectiveness or otherwise of the programmes that teach parents and guardians how to enforce family rules that discourage alcohol and illicit drug use; as well as community-based programmes that combine these components with additional printed and electronic media.